Pengujian Efektivitas Levamisol terhadap Cacing Gastrointestinal pada Ayam Kampung asal Yogya-karta secara in Vitro - Wijayanti, Agustina Dwi; Irawan, Aisha Pasha (IPB University, 2025)
Levamisole is a broad-spectrum anthelmintic from the imidazothiazole derivative group for mammals and poultry. This study aims to evaluate the anthelmintic effectiveness of levamisole against gastrointestinal worms in domestic chickens in Yogyakarta. The findings of this study could potentially lead to the development of more effective strategies for controlling helminthiasis in poultry, thereby improving the health and productivity of domestic chickens. This study is an in vitro laboratory experiment that uses Ascaridia galli (AG) and Raillietina spp. (RL), in a petri dish with ten treatment groups (n=3). The groups consisted of two negative controls, 0.9% sodium chloride AG and RL (G1, G2), two groups of AG and RL in Carboxymethylcellulose Sodium (G3, G4), and levamisole treatment groups with doses of 0.02, 0.1, and 0.2% for three groups of AG (G5-G7) and three groups of RL (G8-G10), respectively. The worm’s mortality time was observed for 24 hours, while descriptive analyses were conducted between treatments with the scoring method. The 0.2% levamisole solution showed anthelmintic efficacy toward AG and RL of a domestic chicken, which in RL has the fastest time to die, 30 minutes of mortality time.